Fostering Sustainable Partnership in the Halal Sector: A Triple Helix Model for Enhanced Food Security and Graduate Employability - Saaidun, Noor Saidatul Natrah binti; Ariffin, Ahmad Shabudin bin; Jamil, Asyraf Isyraqi bin; Nor, Nainatul Farzuha binti (KnE Social Sciences, 2025)
The global food system faces significant challenges in ensuring food security, food safety, and sustainability, which are vital for public health and economic stability. In Malaysia, the halal food supply chain is under increasing pressure to meet the rising demand for Shariah-compliant practices while also addressing sustainability concerns. However, the current system lacks an integrated framework that brings together universities, industries, and government agencies. Furthermore, there is a notable skills gap among graduates, making it difficult for them to meet industry requirements, thereby limiting their employability. Given these challenges, there is an urgent need for a model that not only enhances food security and safety but also improves the employability of graduates through sustainable and Shariah-compliant practice. This research seeks to address these issues by developing a sustainable Shariah-compliant model that enhances Malaysia’s food security and safety. The approach will be grounded in the triple helix model, which fosters collaboration between academia, industry, and government. This model aims to bridge the gap between theoretical knowledge, industrial needs, and government policies. This research uses quantitative research, in the form of surveys among graduates and employers, will explore the existing skill gap and assess metrics related to food safety and security. The expected outcomes of this research are multifaceted. First, it aims to enhance food security by developing a comprehensive model for Shariah-compliant food production that aligns with Malaysia’s sustainability and food safety goals. Second, the employability of graduates will be significantly improved through the acquisition of industry-relevant skills, particularly in the halal sector. Third, the research will strengthen collaboration between academia, industry, and government, leading to more effective knowledge transfer, policy-making, and industrial innovation. Finally, the research will promote sustainability within halal practices, encouraging the halal industry to adopt environmentally friendly methods without compromising Shariah compliance.